Transcranial Stimulation for the Treatment of Stimulant Use Disorder - Amber N. Edinoff; Saveen Sall; T. Dean Roberts; Henry H. Tomlinson; Lenise G. Soileau; Eric D. Jackson; Kevin S. Murnane; Danielle M. Wenger; Elyse M. Cornett; Jaime Toms; Deepak Kumbhare; Adam M. Kaye; et al. (MDPI AG, 2023)
The increasing prevalence of stimulant use disorder (StUD) involving methamphetamine and cocaine has been a growing healthcare concern in the United States. Cocaine usage is associated with atherosclerosis, systolic and diastolic dysfunction, and arrhythmias. Furthermore, approximately one of every four MIs is cocaine-induced among patients aged 18 to 45. Methamphetamine use has been associated with nerve terminal damage in the dopaminergic system resulting in impaired motor function, cognitive decline, and co-morbid psychiatric disorders. Current treatment options for StUD are extremely limited, and there are currently no FDA-approved pharmacotherapies. Behavioral interventions are considered first-line treatment; however, in a recent meta-analysis comparing behavioral treatment options for cocaine, contingency management programs provided the only significant reduction in use. Current evidence points to the potential of various neuromodulation techniques as the next best modality in treating StUD. The most promising evidence thus far has been transcranial magnetic stimulation which several studies have shown to reduce risk factors associated with relapse. Another more invasive neuromodulation technique being studied is deep-brain stimulation, which has shown promising results in its ability to modulate reward circuits to treat addiction. Results showing the impact of transcranial magnetic stimulation (TMS) in the treatment of StUD are limited by the lack of studies conducted and the limited understanding of the neurological involvement driving addiction-based diseases such as StUD. Future studies should seek to provide data on consumption-reducing effects rather than craving evaluations.